[REVIEW] Japan in Australia: Culture, Context and Connections - Alexander Brown (New Voices in Japanese Studies, 2020)
This essay is a review of the book 'Japan in Australia: Culture, Context and Connections', edited by David Chapman and Carol Hayes (Routledge, 2020).